The problem of training school psychologists at the university - Binas, Oksana (Lviv Polytechnic Publishing House, 2015)
Our research is devoted to the professional competences of psychologists in Ukraine. As it turned out, there is no official standarts for this qualification. Therefore, analyzing the international experience, we disscuss the possibility of professional competences as to school psychologists.
Keywords: school psychologist; competence; skills; American students; personality traits